(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
Many alternative substances have been investigated for their potential to replace antibiotics as growth promoters. Probiotics and phytobiotics are some of the products that can be used as growth promoters in broiler. The present study was designed to investigate either single or combined effect of a probiotic and phytobiotic on serum bio-chemistry and growth performances in broilers. A total of 50 Cobb-500 day old chicks were divided into five groups (10 birds each). The birds of Group A were offered a basal diet (corn-soya based), Group B basal diet + 0.10% Renamycin 100®, Group C basal diet + 0.15% probiotic (Bio-Top®), Group D basal diet + 0.10% phytobiotic (Galibiotic) and Group E basal diet + 0.15% Bio-Top® + 0.10% Galibiotic. Body weight, feed intake, weight gain, feed conversion ratio (FCR) and serum bio-chemistry (Triglyceride, cholesterol, LDL, HDL, ALT, AST, creatinine) were recorded. Serum biochemical values differed significantly (P<0.05) among the groups. The average final live weight gain was 665grams, 686grams, 1095grams, 780grams and 1065grams in groups A, B, C, D and E, respectively. The feed conversion ratio was 2.1, 1.96, 1.72, 1.83, and 1.75 in A, B, C, D and E group, respectively. The present study revealed that supplementation of probiotic and phytobiotic in feed significantly reduced triglyceride, cholesterol and HDL values compared to value of control group (P<0.05). Probiotic or its’ combination with phytobiotic has the potential to be exemplary alternatives to antibiotic as growth promoters. Asian Australas. J. Biosci. Biotechnol. 2019, 4 (1), 1-6